Pardon, parole and remission: the inmates’ second chance. - Ahmad Fuzi, Fauziah Hani; Kamarudin, Abdul Rani; Zainal Abidin, Muhammad ‘Azzam (CLJ Law - Legal Network Series, 2018)
For convicted offenders who were not given admonition, fine or bond of good behaviour, they would inevitably end up in prison. Spending time behind iron bars is characterized by rigid disciplines, provision of bare necessities, strict security arrangement, and a monotonous routine life.Despite the Prison Department having rehabilitative programs designed to reform the prisoners from a criminal to a honest life; hence reducing his propensity to commit crimes, the fact is that an imprisonment sentence, especially for a long period, invites other problems too such as prison overcrowding, criminogenic exposure, and unnecessary spending of public funds for the expenditure of the criminals. Thus, to solve these problems and to promote good behaviour of the prisoners while in custody, the authorities introduced the Pardon, Parole, and Remission Systems. These systems aim at giving the prisoners a second chance in the sense that the inmates can have their incarceration period significantly shortened. The objectives and effects of these systems are about the same i.e. to maintain the offenders’ relationship with their families and community as an agent of reform, to reduce the problem of prison overcrowding, and to save public funds. However, the Pardon,Parole, and Remission Systems are relatively not understood by the public i.e. on how they interchangeably function as they are rarely publicised. Due to the lack of understanding of what they are for, it is open wide to a lot of criticisms and questions on the validity of the decisions made by the authorities in respect of these three systems especially when it involves politicians. Therefore, this qualitative based research paper discusses these three systems and how they differ in terms of their application with reference to relevant statutes, decided cases,and media sources. At the end, this paper shows that in the eye of the law, everybody deserves a second chance no matter who he is, and the offender who has served his time will be returning to society.